2001
DOI: 10.1093/wbro/16.2.219
|View full text |Cite
|
Sign up to set email alerts
|

The Politics of Russian Enterprise Reform: Insiders, Local Governments, and the Obstacles to Restructuring

Abstract: Russia and other countries in the Commonwealth of Independent States that have implemented voucher privatization programs have to account for the puzzling behavior of insiders-manager-owners-who, in stripping assets from the firms they own, appear to be stealing from one pocket to fill the other. This article suggests that asset stripping and the absence of restructuring result from interactions between insiders and subnational governments in a particular property rights regime, in which the ability to realize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Shleifer (1998) Che and Qian (1998), for example, suggests that ownership by local government may limit state predation, increase the provision of local public goods, and decrease costly revenue hiding. However, Desai and Goldberg (2001) argue that regional and local governments may impose distortions on enterprises in order to protect local employment. Overall, Cheung et al (2010) note that "the distinction between central and local governments has received little attention in the academic literature" (p. 671), which ultimately makes the effect of ownership by different levels of government an empirical matter.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Shleifer (1998) Che and Qian (1998), for example, suggests that ownership by local government may limit state predation, increase the provision of local public goods, and decrease costly revenue hiding. However, Desai and Goldberg (2001) argue that regional and local governments may impose distortions on enterprises in order to protect local employment. Overall, Cheung et al (2010) note that "the distinction between central and local governments has received little attention in the academic literature" (p. 671), which ultimately makes the effect of ownership by different levels of government an empirical matter.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…This paternalistic relationship between governments and domestic firms maintained through public aid has been a breeding ground for political and bureaucratic corruption involving local firms as well as for ‘state capture’ from the enterprise side (Broadman, 2000; Desai and Goldberg, 2001). 28 The magnitude of this problem has been documented by many studies inside and outside Russia, such as those by Johnson et al (2000, 2002), who confirmed the high prevalence of bribery by local corporate executives in Russia compared with that in Central and East European countries; Chirikova (2001) and Frye (2002a), who clarified the close ties existing between local governments and local enterprises; Golikova et al (2003), who unveiled serious state intervention in private businesses; and Yakovlev and Zhuravskaya (2004), who verified the intensity of state capture practices by business groups by a quantitative analysis based on a unique corporate data set.…”
Section: Market Competition and Management Disciplinementioning
confidence: 99%
“…On the contrary, they are typically active participants in a mutual relationship in which, through law, regulation, or intimidation, firms may be forced to provide concrete political benefits to regional governments in the form of employment and non-wage benefits for both employees and the general public (Desai and Goldberg, 2001). In particular, the absence of a well-functioning social safety net, either nationally or sub-nationally, has prompted regional governments to use firms as surrogate sources of social services.…”
Section: Fiscal Federalism In the Russian Federationmentioning
confidence: 99%